(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the operational impacts of workforce diversity within small and medium-sized enterprises (SMEs) in North-East Odisha, a region characterized by its diverse cultural and economic landscape. Recent literature underscores the potential of diverse teams to enhance innovation and decision-making processes, yet SMEs in emerging markets often encounter unique challenges that may complicate these benefits. This paper aims to explore how these dynamics manifest in the context of North-East Odisha, seeking to identify specific operational outcomes linked to workforce diversity. Methodology: Employing a structured equation modeling approach, this research utilizes data collected from 250 respondents through purposive sampling. The sample includes a mix of owners, managers, and employees from various SMEs across North-East Odisha. Variables measured include demographic diversity (age, gender, ethnicity), perceived team effectiveness, innovation rates, and financial performance. The analysis aims to untangle the relationships between these variables, providing a nuanced understanding of how diversity impacts operational outcomes. Results: Preliminary analysis reveals a complex relationship between workforce diversity and operational effectiveness among SMEs in the region. While some degree of diversity correlates positively with innovation and team effectiveness, excessive heterogeneity appears to impede communication and operational efficiency. Financial performance indicators show varied results, suggesting that the benefits of diversity might depend on specific contextual factors like industry type and enterprise size. Conclusion: The findings suggest that workforce diversity has a multifaceted impact on the operations of SMEs in North-East Odisha. While diversity fosters innovation and can enhance team effectiveness, there is a threshold beyond which it may start to hinder operational performance. These insights underscore the need for SMEs to adopt tailored diversity management strategies that recognize the specific socio-economic conditions of North-East Odisha. Future research should explore longitudinal data to better understand the long-term effects of diversity on SME performance in the region.